2014
DOI: 10.1097/bpo.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Diagnosis, and Treatment of Pericapsular Pyomyositis of the Hip in Children

Abstract: Level II-"Diagnostic" [Development of diagnostic criteria on the basis of consecutive patients (with universally applied reference "gold" standard)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…Including all types of musculoskeletal infection in the prognostic model reflects clinical practice. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Including all types of musculoskeletal infection in the prognostic model reflects clinical practice. 11 …”
Section: Discussionmentioning
confidence: 99%
“…13 It is also important to differentiate septic arthritis from extra-articular infection. 16 MRI could provide a precise diagnosis enabling debridement of the epicentre of infection and thus preventing a prolonged infectious process as well as avoiding unnecessary debridement of the joint and joint contamination. 16 As we suspected an osteitis on the right side clinically, we started the relevant broad spectrum antibiotics (cloxacillin and cefotaxime).…”
Section: Discussionmentioning
confidence: 99%
“…16 MRI could provide a precise diagnosis enabling debridement of the epicentre of infection and thus preventing a prolonged infectious process as well as avoiding unnecessary debridement of the joint and joint contamination. 16 As we suspected an osteitis on the right side clinically, we started the relevant broad spectrum antibiotics (cloxacillin and cefotaxime). Usually our protocol is to drain the collection as soon as possible -in a similar case we would have opened the hip and knee joint -if these were both negative the femur would have been drilled to decompress any intramedullary pus collection.…”
Section: Discussionmentioning
confidence: 99%
“…3 They found that peri-capsular pyomyositis presented twice as often as septic arthritis (32% vs. 15% respectively). 3 This further illustrates the need to differentiate various hip pathologies other than septic arthritis as reducing the time to commence treatment may be important in avoiding complications of pyomyositis.…”
Section: Dear Editor Early Use Of Mri For Suspected Pyomyositismentioning
confidence: 99%
“…[3][4][5] MRI is superior to ultrasound when imaging the pelvis as it excludes other local pathology.…”
Section: Dear Editor Early Use Of Mri For Suspected Pyomyositismentioning
confidence: 99%